Universal Design for Learning and Inclusive Teaching: Future Perspectives - Martina Rossi (Elementa, 2022)
This contribution aims to reflect on the didactic and methodological changes brought about by Distance Learning, with particular regard to the concept of Inclusive Teaching. During the last year, in fact, the epidemiological emergency dictated by Covid-19 has led to the emergence of new needs, imposing a redesign of tools and resources in use. All this has had a strong impact on students with disabilities and Specific Learning Disorders (SLD), who, in addition to having fewer digital skills than their European peers, were suddenly forced to follow lessons at home without the physical support of the teacher. It was necessary, in fact, to think and re-think about the design of inclusive educational interventions. From a methodological and conceptual point of view, Inclusive Teaching is linked to the concept of Universal Design for Learning (UDL), an inclusive psycho-pedagogical approach that aims to break down the barriers that exist in learning processes. During the pandemic period, one of the major challenges that scholars have begun to consider is applying the UDL approach, generally used in in-person classes, lectures and online courses.